Helicobacter pylori Infections in Children - Julie Nguyen; Kallirroi Kotilea; Patrick Bontems; Veronique Yvette Miendje Deyi (MDPI AG, 2023)
In the context of epidemiology, host response, disease presentation, diagnosis, and treatment management, the manifestation of Helicobacter pylori (H. pylori) infection diverges between children and adults. H. pylori infection stands out as one of the most prevalent bacterial infections globally, and its prevalence in both children and adults is decreasing in many developing countries but some still struggle with a high prevalence of pediatric H. pylori infection and its consequences. The majority of infected children are asymptomatic and pediatric studies do not support the involvement of H. pylori in functional disorders such as recurrent abdominal pain. The pathophysiology of H. pylori infection relies on complex bacterial virulence mechanisms and their interaction with the host immune system and environmental factors. This interaction gives rise to diverse gastritis phenotypes, which subsequently influence the potential development of various gastroduodenal pathologies. In clinical settings, the diagnosis of this infection in childhood requires an upper gastrointestinal endoscopic exam with mucosal biopsy samples for histology and culture, or Polymerase Chain Reaction (PCR) at the very least. When warranted, eradication treatment should be given when good compliance is expected, and there should be systematic use of a treatment adapted to the antimicrobial susceptibility profile. To combat the burgeoning threat of multidrug resistance, vigilant surveillance of resistance patterns and strategic antibiotic management are paramount.